Emerging technologies and the democratisation of financial services: A metatriangulation of crowdfunding research. Issue 4 (December 2016) - Gleasure, Rob; Feller, Joseph
Abstract: Crowdfunding has grown quickly and attracted significant scholarly attention. However, the diverse approaches to crowdfunding that have emerged, as well as the uncertain relationship of these approaches to the umbrella concept of crowdsourcing, means it is not clear to what extent crowdfunding presents theoretically novel behaviours, nor what those behaviours may be. This study addresses this lack of clarity through a metatriangulation of 120 peer-reviewed studies on crowdfunding. These studies are distributed across the four dominant categories of crowdfunding, namely crowd lending, crowd equity, crowd patronage, and crowd charity. Research for each category is analysed separately to determine the topics of interest, the dominant theoretical perspectives, the methods employed, and the typical focus of analysis. We bridge these categories to identify three common variables relating to funding behaviours and three relating to impact. Of these, we argue that two are fundamentally novel and under-researched, namely the 'erosion of organisations' financial boundaries' and 'paying to participate'. The implications of these findings are discussed for crowdfunding and crowdsourcing. Highlights: Multiple paradigms of crowdfunding research have emerged. A metatriangulation is used to identify what, if anything, is new about crowdfunding. Users are willing to pay to participate in interesting projects. Organisations are decreasing in financial entitativity.